Interregional Poverty Linkages and Human-Capital Correlates in the Special Region of Yogyakarta: Evidence from a Spatial Panel Model - Safaat Yulianto; Atika Nurani Ambarwati; Virgania Sari; Aning Azizah Wijayanti; Nadia Resky Reza Az-zahra (UIN Sumatera Utara, 2026)
Poverty remains unevenly distributed across the Special Region of Yogyakarta (DI Yogyakarta), suggesting that local conditions and interregional linkages may shape poverty outcomes. This study examined poverty rates across five regencies/city administrative units in DI Yogyakarta during 2021-2025 while accounting for spatial dependence. A balanced panel was analyzed by comparing common, fixed, and random effects models, followed by spatial diagnostics and estimation of a spatial autoregressive fixed-effects model. The average poverty rate declined from 13.28% in 2021 to 10.61% in 2025. Under model-based inference, the spatial lag coefficient was positive (rho = 0.629), indicating spatial association in poverty rates across neighbouring regions. The spatial impact decomposition showed that expected years of schooling had negative direct, indirect, and total effects on poverty, whereas the effects of mean years of schooling, literacy rate, life expectancy at birth, and stunting prevalence were weaker. The findings are interpreted as exploratory, context-specific associations.